2018
DOI: 10.1002/anie.201807093
|View full text |Cite
|
Sign up to set email alerts
|

Iron Scavenging in Aspergillus Species: Structural and Biochemical Insights into Fungal Siderophore Esterases

Abstract: Fungi utilize high-affinity chelators termed siderophores with chemically diverse structures to scavenge the essential nutrient iron from their surroundings. Since they are among the strongest known Fe binding agents, intracellular release of the heavy metal atom is facilitated by the activity of specific hydrolases. In this work, we report the characterization and X-ray crystal structures of four siderophore esterases: AfEstB and AfSidJ from Aspergillus fumigatus, as well as AnEstB and AnEstA from Aspergillus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…Kinetic assays using TAFC as the substrate demonstrated that the MBPtagged form of the enzyme was active, and LC−MS studies showed that the enzyme cleaves Fe 3+ -bound TAFC into its corresponding building blocks (Figure 3) as previously described. 20 Application of AfEstB to ginseng roots infected with I. morspanacis significantly reduced the severity of infection (Figures 4 and 5). These results show that enzymatic treatment decreases virulence and slows the growth of the fungus.…”
Section: ■ Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Kinetic assays using TAFC as the substrate demonstrated that the MBPtagged form of the enzyme was active, and LC−MS studies showed that the enzyme cleaves Fe 3+ -bound TAFC into its corresponding building blocks (Figure 3) as previously described. 20 Application of AfEstB to ginseng roots infected with I. morspanacis significantly reduced the severity of infection (Figures 4 and 5). These results show that enzymatic treatment decreases virulence and slows the growth of the fungus.…”
Section: ■ Discussionmentioning
confidence: 71%
“…These results are in accordance with previously published values for the isolated recombinant enzyme. 20 We also monitored AfEstB activity by tracking the degradation of TAFC via high-resolution LC−MS (Figure 3C). AfEstB hydrolyzes the ester moieties that link the three acetylated ornithine units that comprise TAFC.…”
Section: ■ Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“… A. fumigatus has a virulence-required siderophore-mediated iron acquisition system ( 26 ). The major secreted siderophore is triacetylfusarinine C (TAFC) ( 27 , 28 ), which is inducibly secreted under iron-deficient conditions. In A. fumigatus , iron uptake, consumption and detoxification must be tightly controlled.…”
Section: Introductionmentioning
confidence: 99%